Artificial Intelligence and the Future of Intellectual Property Law: A Critical Review - Dodi Rusmana; Rashid Rahman; Nina Anis (Rechtsnormen: Journal of Law, 2026)
Background. The rapid development of artificial intelligence has profoundly transformed creative and innovative practices, raising complex challenges for existing intellectual property law frameworks. Legal regimes governing copyright and patents were historically constructed around human authorship, inventorship, and intentional creativity, assumptions that are increasingly strained by the emergence of autonomous and generative AI systems. Purpose. This study aims to critically review how contemporary intellectual property law responds to the growing role of artificial intelligence and to assess whether current doctrines remain conceptually and normatively adequate. Method. The research adopts a qualitative doctrinal and critical review method, analyzing statutes, policy documents, judicial decisions, and peer-reviewed literature related to artificial intelligence and intellectual property law across multiple jurisdictions. Results. The findings reveal persistent legal uncertainty, doctrinal rigidity, and fragmented regulatory approaches, with most legal systems favoring reinterpretation of human-centric concepts rather than substantive reform. The analysis also highlights significant divergence between jurisdictions in balancing innovation incentives, ethical concerns, and legal certainty. Conclusion. The study concludes that incremental doctrinal adaptation alone is insufficient to address the structural challenges posed by artificial intelligence. A more integrated and forward-looking legal framework is required to reconcile technological autonomy with the foundational objectives of intellectual property law and to ensure its continued relevance in the age of artificial intelligence.